Innovation analysis in a cooperative from the Sustainable Development Dimensions - Tomazzoni, Gean Carlos; Santos, Rita de Cássia Trindade dos; Santos, Andressa Schaurich dos; Costa, Vânia Medianeira Flores (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The theme of sustainable development has historically gained the interest of civil society organizations and academia and industry, however, is a huge challenge to put into practice the concept formed by the complementarity between development and sustainability. Thus, this study aims to identify the product, process and management innovations implemented by a dairy cooperative, and its impact on economic, social and environmental dimensions. This study is characterized as descriptive and qualitative approach. Therefore, there was a semi-structured interview, adapted from Delgado (2007), with the administrative and financial manager of an organization of the dairy sector, located inside the Rio Grande do Sul State. Initially we attempted to map the innovations product, process and management implemented in the organization in the years 2011 to 2013. Later, we sought, based on the respondent perceptions, what were the impacts of each of the innovations mapped in economic spheres, environmental and social sustainable development. The main findings of the study show that the innovations implemented by the organization are directed to the acquisition of new machinery and upgrading of infrastructure. Mapped innovations generated impacts mainly for the social and economic spheres of sustainable development.